Poly(Vinylidene Fluoride) Nanofiber Array Films with High Strength for Effective Impact Energy Harvesting. Issue 11 (3rd October 2021) - Bai, Zikui; Song, Yuxian; Peng, Jiashun; Chen, Dongzhi; Zhou, Yingshan; Tao, Yongzhen; Gu, Shaojin; Xu, Jie; Deng, Zhongmin; Yin, Xianze; Xu, Weilin
Abstract : Absorbing high mechanical impact energy and converting it into electrical energy is challenging due to the low efficiency and strength of the existing piezoelectric generators. Here, a new type of piezoelectric nanogenerator is reported that is a sandwich structure composed of upper and lower electrodes and a poly(vinylidene fluoride) (PVDF) nanofiber array film. The PVDF nanofiber array films with dense vertical alignment characteristics are successfully fabricated by a combination of electrospinning and cutting methods. Each nanofiber in the nanofiber array film becomes an independent nanogenerator with an equivalent piezoelectric response which greatly enhances the charges collection and energy conversion efficiency of the nanogenerator. The maximum instantaneous power density of 26.3 μW cm −2 can be reached under the impact of the 9.1 g ball falling freely from a height of 20 cm. The nanofiber array structure endows the piezoelectric nanogenerator with high mechanical strength in the normal direction of the surface and excellent stability. Furthermore, the power output of two parallel‐connected nanogenerators (1.5 × 1.5 cm 2 each) can light up 12 LEDs without storage devices. The unique properties of the piezoelectric nanogenerator offer great potential for high mechanical impact energy harvesting and effective conversion. Abstract : Herein, a piezoelectric nanogenerator based on poly(vinylidene fluoride) nanofiber array films with dense vertical alignment characteristics is reported. Each nanofiber in the nanofiber array films is an equivalent independent nanogenerator which greatly enhances the charges collection and energy conversion efficiency of the nanogenerator. Under the impact of small ball, the instantaneous power density reaches 26.3 μW cm −2 .